2019
DOI: 10.1016/j.proci.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Spherical turbulent flame propagation of pulverized coal particle clouds in an O2/N2 atmosphere

Abstract: This study aimed to clarify the effects of turbulence intensity and coal concentration on the spherical turbulent flame propagation of a pulverized coal particle cloud. A unique experimental apparatus was developed in which coal particles can be dispersed homogeneously in a turbulent flow field generated by two fans. Experiments of spherical turbulent flame propagation of pulverized coal particle clouds in a constant volume spherical chamber in various turbulence intensities and coal concentrations were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…Fuel ratio is the ratio of fixed carbon to volatile matter. In coal-O₂ N₂ (pure coal) cloud combustion, NH₃ -O₂ N₂ (pure ammonia) combustion, and NH₃ -O₂ N₂ -coal (ammonia/coal particle) cloud co-combustion, diluted oxygen (40 vol% O2 and 60 vol% N2) was used as the ambient gas, similar to the pure coal combustion [13]. The flame propagation behavior of ammonia/coal particle cloud co-combustion was simultaneously recorded by direct imaging and OH radical imaging through the same window, as shown in Fig.…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuel ratio is the ratio of fixed carbon to volatile matter. In coal-O₂ N₂ (pure coal) cloud combustion, NH₃ -O₂ N₂ (pure ammonia) combustion, and NH₃ -O₂ N₂ -coal (ammonia/coal particle) cloud co-combustion, diluted oxygen (40 vol% O2 and 60 vol% N2) was used as the ambient gas, similar to the pure coal combustion [13]. The flame propagation behavior of ammonia/coal particle cloud co-combustion was simultaneously recorded by direct imaging and OH radical imaging through the same window, as shown in Fig.…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…Therefore, the pyrolysis rate of coal particles can be increased by heat transfer from flame propagation of ammonia with the addition of volatile matter in ammonia/coal particle cloud co-combustion. Hadi et al [13] suggested that the increase of turbulent heat transfer increased the flame propagation velocity of coal particle clouds. Volatile combustion has been investigated by many researchers [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…1 shows a schematic diagram of the experimental apparatus used in this study. Experiments were carried out using a constant volume combustion chamber that has a volume of about 6.2 L [36]. The interior of the combustion chamber was spherical with a diameter of 200 mm.…”
Section: Experimental Apparatus and Proceduresmentioning
confidence: 99%
“…The integration can be calculated using the Gamma function, Γ, as expressed by Eq. ( 7): The longitudinal integral length scale, , was calculated as = 20.9 mm regardless of the turbulence intensity [36].…”
Section: Turbulence Characteristicsmentioning
confidence: 99%
“…Accordingly, our research group recently started to conduct the fundamental research on the mixed combus-tion characteristics of ammonia with pulverized coal particle cloud (Hashimoto N. et al, 2019a(Hashimoto N. et al, , 2019b. The flame propagation characteristics of an ammonia-coal particle cloud in turbulent fields has been investigated by using a fan-stirred constant volume vessel (Hadi K. et al, 2019). The developments of the mixing combustion models using the experimental results from these researches for the ammonia-coal particle cloud mixture for numerical simulations is expected in the near future.…”
Section: Fig 25mentioning
confidence: 99%